The Performance of Sub-District Office Employees in South Nias That Influenced by The Work Environment and Job Stress Through the Mediation of Job Satisfaction - Duha, Timotius (Jurnal Mebis, 2025)
This study aims to investigate the influence of the work environment and work stress on employee performance, as mediated by job satisfaction. This type of research is quantitative, with data analysis using path analysis through partial least squares, while data processing is carried out using Smart PLS software. The population determined was all representatives of the sub-district office in three sub-districts (Telukdalam, Fanayama, and Amandraya), totaling 89 people. The questionnaire was distributed to the entire population, but only 77 copies were returned. The results of the study showed that directly, the work environment and stress had a positive effect on job satisfaction and performance, and indirectly, through the mediation role of job satisfaction, the work environment and work stress had a positive effect on performance. Practical Implications of this study: Strong synergy among representatives should be used as a strength in producing job satisfaction, even in sudden and urgent work situations. It is hoped that job satisfaction can boost employee performance. Research Limitations: The number of research locations is still limited, hopefully in the future it can be increased so that it can represent more representatives of the sub-district office in South Nias.